Adult and adolescent exposure to tobacco and alcohol content in contemporary YouTube music videos in Great Britain: a population estimate - Cranwell, Jo; Opazo-Breton, Magdalena; Britton, John (BMJ Publishing Group, 2016)
Background: We estimate exposure of British adults and adolescents to tobacco and alcohol content from a sample of popular YouTube music videos.